الاستفادة منها في تعليم اللغة العربية للومبوكيين SASAK-INDONESIA الكلمات الساساكية ذات أصل عربي في معجم - Muzamiludin; Nuradi (Lembaga Penelitian dan Pengabdian Masyarakat, Sekolah Tinggi Ilmu Bahasa Arab Ar Raayah, 2018)
Language Absorption is something that available in all Language because Languages is something lives, develops, and the absorption is not limited in only an official language of a country, but includes regional languages ​​as well as in the Sasak language. To complete this research the researcher used analytical descriptive method that appropriate with the research, because this research was aimed for collecting sasak’s, vocabulary wich from arabic in the Kamus Bahasa Sasak-Indonesia letters A to J and analyzing meaning alteration, pronuncing, and composition, and then use it to teaching Arabic for Lombok’ people. And the result of this research indicate that there seventy one sasak language’s vocabularies that from arabic divided into Four parts according to meaning Changes and the forms Sasak Language: 1) Vocabulary that contains the same meaning as in Arabic, example: word “AKIL” and